STUDI LEMBAGA PENDIDIKAN SUFISTIK MASA ISLAM KLASIK - Muhammad Riduan Harahap (STIT Al-Ittihadiyah Labuhanbatu Utara, 2019)
This paper concludes that the center of Sufi activity in its early emergence is commonly referred to as ribath, zawiyah and khanqah which came to be known as Sufistic educational institutions. While related to the curriculum or material taught and studied in Sufistic educational institutions, both ribathh, zawiyah, and the khanqah, as stated by Trimingham is the material of the Qur'an, the science of interpretation, hadith, fiqh, and principles Sufism. Other material taught in Sufi institutions is legal studies. This is as for example taught in zawiyah ash-Sharia where there is a madrasa for tullab (students who study law. At one time there were about 200 students, 29 of whom were blind). In addition, in ribath taught for example also about reading, writing, religious sciences, and Sufism. In khanqah also taught other materials such as', auditions, poetry, music, and ecstatic dances which are integrated into the worship of Sufis. Meanwhile, the educational process that takes place at these institutions uses the method as is generally used in other classical Islamic educational institutions. The most frequently used methods are methods that are more relevant to the world of Sufism, such as memorization, riyadah / exercises, and sima'an (listening) methods. In khanqah, dialog and conversation methods are also used, where this method is one of the methods which is used in the world of Islamic education. In addition, the halaqah method is another method inherent in the education process in the three institutions.